(untitled) (Albayan Scientific Journal, 2024)
This study was an attempt to explore Libyan students’ views about the use of electronic learning as a pedagogical tool in a language classroom at Sirte university. It also attempted to find out the obstacles that EFL students face when using electronic learning. The research instrument used in this study consisted of a close-ended questionnaire which consisted of ten statements and questions, and 12 sub-statements. The sample of this study consisted of thirty EFL learners who were randomly selected from the College of Education, the English Department at Sirte University. The data was collected and analyzed quantitatively. Based on the findings of this study, it can be said that students are aware of the importance of using E-learning, yet they are not having the proper chance to use them for different reasons. It can also be concluded that students at Sirte University-college of Education encounter several pedagogical and technical obstacles and challenges when using electronic learning.